Protection of industrial power systems - Davies, T.
The protection which is installed on an industrial power system is likely to be subjected to more difficult conditions than the protection on any other kind of power system. Starting with the many simple devices which are employed and covering the whole area of industrial power system protection, this book aims to help achieve a thorough understanding of the protection necessary. Vital aspects such as the modern cartridge fuse, types of relays, and the role of the current transformer are covered and the widely used inverse definite-minimum time overcurrent relay, the theory of the Merz-Price p.